2013
DOI: 10.4172/2155-9880.s11-007
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Cardiac Stem Cell Therapy for Ischemic Heart Failure

Abstract: Cardiovascular disease remains the number one cause of morbidity and mortality in the world. With great advances in medical and interventional therapies, patients who suffer from acute myocardial infarction have a longer life expectancy than before, but gradually develop chronic heart failure in their later life due to irreversible loss of cardiomyocytes. So far, heart transplantation is the only therapeutic option for advanced heart failure. However, the shortage of donor organs largely limits its role as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…Secondly, these cells could be successfully administered by intracoronary injection to patients with prior MI [ 67 , 69 , 71 ]. For autologous transplantations, CSCs are usually isolated from atrial appendages and ventricular and epicardial biopsies [ 72 ]. However, since atrial and ventricular cardiomyocytes have differential gene expression and functional efficacy, it is not known whether the stem cells from atria and ventricles have the same characteristics and functions [ 73 ].…”
Section: Stem Cells From Different Sources In the Treatment Of Cardiomentioning
confidence: 99%
“…Secondly, these cells could be successfully administered by intracoronary injection to patients with prior MI [ 67 , 69 , 71 ]. For autologous transplantations, CSCs are usually isolated from atrial appendages and ventricular and epicardial biopsies [ 72 ]. However, since atrial and ventricular cardiomyocytes have differential gene expression and functional efficacy, it is not known whether the stem cells from atria and ventricles have the same characteristics and functions [ 73 ].…”
Section: Stem Cells From Different Sources In the Treatment Of Cardiomentioning
confidence: 99%
“…N ‐(3‐dimethylaminopropyl)‐ N ′‐ethylcarbodiimide hydrochloride (EDC)/ N ‐hydroxysuccinimide (NHS) crosslinking route also offers advantages such as zero‐length crosslinks, preservation of triple helix structure, close control over reaction conditions, and water‐soluble by‐products . Moreover, cardiosphere‐derived cells (CDCs), selected in this study, are an endogenous population present in the adult heart with differentiation affinity into myocytes, smooth muscle cells, and endothelial cells (EC) . Their therapeutic efficacy has been established in animal models and a clinical trial reported reduced area of damage in CDC‐treated patients …”
Section: Introductionmentioning
confidence: 99%
“…[28,29] Moreover, cardiosphere-derived cells (CDCs), selected in this study, are an endogenous population present in the adult heart with differentiation affinity into myocytes, smooth muscle cells, and endothelial cells (EC). [30,31] Their therapeutic efficacy has been established in animal models [32,33] and a clinical trial reported reduced area of damage in CDC-treated patients. [34,35] In this study, it has been hypothesized that heterogeneous hybrid scaffolds with varying crosslinking densities could be developed using a multistep sequential crosslinking technique based on EDC/NHS.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac stem cells (CSCs), identified in the heart in 2003 [2,3], are primed to repair damaged myocardium, but are able to replace only a small proportion of the cells in the heart per year [4][5][6]. To provide sufficient cells for therapy, CSCs can be expanded in vitro, after selection using cell surface markers, such as c-kit [3] or Sca-1 [2], or from explanted biopsies via the formation of cardiospheres [7,8].…”
mentioning
confidence: 99%